(5x-3)(x+4)-(2x+5)(3x-4)
Answers
Answered by
8
Answer:
Answer is x² - 10x - 8......
Step-by-step explanation:
- (5x-3)(x+4)-(2x+5)(3x-4)
- = (5x² + 20x -3x -12) - ( 6x² - 8x + 15x - 20)
- = 5x² + 20x -3x -12 - 6x²+ 8x - 15x + 20
- = -x² + 10x +8
- = x² - 10x - 8
Answered by
2
Answer:
hope it will help you please mark me as a brilliant
Attachments:
![](https://hi-static.z-dn.net/files/db0/310bde9b2097504e81cf874c28e4daf6.jpg)
![](https://hi-static.z-dn.net/files/d4f/b5a4ce0cd8249f193a4ce3c9ff385768.jpg)
Similar questions